2021
DOI: 10.3389/fgene.2021.674613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MAP3K8 on Prognosis and Tumor-Related Inflammation in Renal Clear Cell Carcinoma

Abstract: Background: MAPK kinase kinase 8 (MAP3K8) is involved in the regulation of MAPK cascades and immune responses. Differential expression of MAP3K8 is closely correlated with tumorigenesis. In this study, we used bioinformatics tools to explore expression level, prognostic values, and interactive networks of MAP3K8 in renal clear cell carcinoma (ccRCC).Methods: Differential expression of MAP3K8 was determined by TIMER2.0, UALCAN, and Oncomine Platform. For exploration of MAP3K8 mutation profile, TIMER2.0, DriverD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The XCELL ( Aran et al, 2017 ), TIMER ( Li et al, 2017 ), QUANTISEQ ( Hao et al, 2021 ), MCP-counter ( Becht et al, 2016 ), EPIC ( Racle and Gfeller, 2020 ), CIBERSORT−ABS ( Xu Q. et al, 2021 ), and CIBERSORT ( Chen et al, 2018 ) algorithms were used to assess the levels of various tumor-infiltrating immune cells: endothelial cells, hematopoietic stem cells, common myeloid progenitors, macrophages, activated mast cells, monocytes, central memory CD4 + T cells, neutrophils, memory B cells, cancer-associated fibroblasts, plasma B cells, M0 macrophages, M1 macrophages, activated natural killer (NK) cells, nonregulatory CD4 + T cells, activated memory CD4 + T cells, and so on.…”
Section: Methodsmentioning
confidence: 99%
“…The XCELL ( Aran et al, 2017 ), TIMER ( Li et al, 2017 ), QUANTISEQ ( Hao et al, 2021 ), MCP-counter ( Becht et al, 2016 ), EPIC ( Racle and Gfeller, 2020 ), CIBERSORT−ABS ( Xu Q. et al, 2021 ), and CIBERSORT ( Chen et al, 2018 ) algorithms were used to assess the levels of various tumor-infiltrating immune cells: endothelial cells, hematopoietic stem cells, common myeloid progenitors, macrophages, activated mast cells, monocytes, central memory CD4 + T cells, neutrophils, memory B cells, cancer-associated fibroblasts, plasma B cells, M0 macrophages, M1 macrophages, activated natural killer (NK) cells, nonregulatory CD4 + T cells, activated memory CD4 + T cells, and so on.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, many studies have found that inflammatory cells and factors play an important role in the development, transformation and metastasis of tumors, including inflammatory cells, chemokines, their receptors and downstream signaling pathways 31–34 . ccRCC is a typical immunogenic tumor with abundant immune cell infiltration 35 .…”
Section: Discussionmentioning
confidence: 99%
“…We explored the association between the KDM6B expression and immune infiltration across all tumors in TCGA with TIMER2.0. CIBERSORT, CIBERSORT-ABS, TIMER, quanTIseq, MCP-counter, xCell, and EPIC algorithms ( Hao et al, 2021 ) were applied to evaluate the immune infiltration data in all tumors across all immune cells in TIMER2.0, including monocytes, mast cells, macrophages, CD4 + T cells, CD8 + T cells, Treg, follicular helper T cells, NK T cells, NK cells, neutrophils, common lymphoid progenitors, hematopoietic stem cells, common myeloid progenitors, endothelial cells, DCs (dendritic cells), granulocyte–monocyte progenitors, myeloid-derived suppressor cells, eosinophils, and cancer-associated fibroblasts. The purity-adjusted Spearman’s rank correlation test was used to obtain the p -values and sectional correlation values.…”
Section: Methodsmentioning
confidence: 99%